Cervical human papillomavirus DNA detection in women living with HIV and HIV-uninfected women living in Limbe, Cameroon - Adedimeji, Adebola (J Clin Virol, 2020)
BACKGROUND. There are limited data on cervical HPV prevalence in Cameroon and none from its Anglophone region. We investigated cervical HPV prevalence in HIV-uninfected (HIV[−]) and HIV-infected (WLWH) women living in the region. METHODS. A convenience sample of consecutively recruited HIV[−] women (n=295) and women living with HIV (WLWH) (n=560) attending the Limbé Regional Hospital were enrolled into a cervical screening study. Women underwent screening that included HPV testing of self-collected and provider-collected specimens. We calculated the HPV prevalence by HIV status, overall and stratified by age, and among WLWH, stratified by CD4 counts. We compared the concordance for the detection of HPV between self- and provider-collected specimens. RESULTS. Crude HPV prevalence was 21.69% (95% confidence interval [95%CI]=17.21–26.48%) for HIV[−] women and 46.43% (95%CI=42.24–50.66%) for WLWH (p<0.001). Among WLWH, older age (p(trend)=0.01) and higher CD4 counts (p(trend)=0.007) were associated with lower HPV prevalence. There was a good-to-excellent agreement for HPV detection between specimens, and self-collected were more likely than provider-collected specimens to test HPV positive, for all women and stratified by HIV status. CONCLUSIONS. HIV-related immunosuppression was a risk factor for HPV prevalence in this population. HPV testing of self-collected specimens appeared to be less specific than HPV testing of provider-collected specimens.